The Impact of Teaching Jurisprudence by Using Storytelling in Developing the Imagination Skills among the Sixth Intermediate Students in the Kingdom of Saudi Arabia - Al Shehri, Zafer Suleiman Nasser (Journal of Educational and Psychological Sciences, 2018)
The study aimed to investigate the effect of teaching jurisprudence by using narrative narratives to improve the imaginative skills of sixth graders in the Kingdom of Saudi Arabia. The study sample consisted of (40) students who were chosen by the intentional method of Qadisiya primary school in the town of " In the Kingdom of Saudi Arabia, and were randomly distributed to two groups of control and experimental (20) students in each group, the study used narrative narrative strategy in the teaching of the ninth unit (Hajj and Umrah) of the book of jurisprudence of the experimental group, Jmuah the control unit of study in the usual way, In order to achieve the objectives of the study, the researcher prepared the study tool, which is a test of my essay to measure the skills of imagination, which consists of (11) paragraphs. The researcher also reconstructed the contents of the unit in four stories, The results showed statistically significant differences at (α = 0.05) between the performance of the experimental group and the performance of the students of the control group due to the teaching strategy used, There were statistically significant differences between the mean of the experimental group and the control group for the experimental group. These results indicate that there are statistically significant differences in the development of the skills of imagination and achievement among sixth graders in the Kingdom of Saudi Arabia due to the narrative narrative strategy used in teaching. Thus, it can be said that the use of strategy narrative narrative in the teaching of jurisprudence leads to the development of imagination skills among sixth grade students in the Kingdom of Saudi Arabia. The study recommended the use of teaching strategies to help develop the imagination skills of students in different educational stages.
Keywords: impact; storytelling; imagination; jurisprudence; sixth grade of primary school